Pengaruh Metode Pembelajaran Game Based Learning terhadap Minat Belajar Mata Pelajaran Akidah Akhlak MAN 3 Agam - Fadhilah, Nurul; Rahmi, Ulva (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Students engage in more than just receiving and listening to the teacher's explanations throughout the learning process. It is also necessary for students to actively engage in the learning process. Using a game-based approach to teach Aqidah Akhlak helps motivate pupils to participate more in class. The purpose of this study is to determine the extent to which the use of game-based learning techniques affects students' active learning in the Islamic Religious Education class XII Science at MAN 3 Agam. Utilizing a one-group pretest-posttest design and the Pre-Experiment approach, this study is quantitative in nature. There are two variables in this study: the dependent variable is learning interest, and the independent variable is the game-based learning approach. The students who completed the questionnaire were the ones that provided the data. Using purposive sampling, a sampling approach, the study's sample consisted of 25 students out of the total population of 69 pupils. There is a significant difference between the dependent and independent variables when the decision-making has a significant value less than 0.05. When considering the student questionnaire, the sig value comes out at 0.001, indicating a substantial impact on the treatment differences for each variable. It follows that the adoption of game-based learning techniques influences students' curiosity in Aqidah Akhlak class XI Science at MAN 3 Agam.